CONSTRUCTION OF RECOMBINANT PLASMID FOR EXPRESSION OF THE GENE ENCODING XYLANASE GH43 OF BACILLUS AMYLOLIQUEFACIENS ABBD - Sri Rahayu, Rizky
Xylanase is an enzyme that randomly breaks the ?-1,4 glycosidic bonds in xylan polymers into xylose and xylo-oligosaccharides (XOS). Xylan is a major component of hemicellulose, the largest biomass on earth, thus xylanase has been widely applied in the food, fuel, animal feed, and paper industries. In a previous study, a GH43 family xylanase encoding gene (xil43) was obtained from the genome of Bacillus amyloliquefaciens ABBD, measuring 1488 bp. The aim of this study is to construct the recombinant plasmid pET-16b-xil43 and express the xil43 gene in Escherichia coli. To achieve this research objective, xil43 from the previous study was amplified to add enzyme cutting sites compatible with the expression vector. The next step was the amplification of xil43 with added enzyme cutting sites through cloning, and the results were confirmed by colony PCR, restriction analysis, and nucleotide sequence determination. The subsequent step was subcloning the xil43-restriction sites with the pET-16b expression vector, characterized by colony PCR and nucleotide sequence determination. The next process was the expression of pET-16b-xil43 in E. coli ArcticExpress (DE3) cells and purification of GH43 xylanase. Amplification of xil43-restriction sites was successfully performed using PCR (Polymerase Chain Reaction) with an optimal primer annealing temperature of 46.7°C, and the nucleotide sequence matched the database. This result was then subcloned with pET16b xil43 plasmid to produce the recombinant plasmid pET16b-xil43. The nucleotide sequence of xil43 in pET16b-xil43 also matched the database. This pET16b-xil43 was successfully used to transform E. coli ArcticExpress (DE3). Expression of pET16b-xil43 with 0.1 mM IPTG inducer at 10°C for 16–18 hours resulted in a thick band of 54.8 kDa on the SDS-PAGE electropherogram. The crude extract solution from lysed E. coli ArcticExpress (DE3)-pET16b xil43 cells (soluble fraction) also showed xylanase activity using 1% (w/v) beechwood xylan with a specific activity of 0.379±0.003 U/mg. GH43 xylanase was also successfully purified using Ni-NTA affinity chromatography, resulting in a single band on the SDS-PAGE electropherogram.